TROPHONOPSIS BUCQUOY, DAUTZENBERG AND DOLLFUS, 1882 (GASTROPODA, MURICIDAE) FROM THE PLIO-PLEISTOCENE DEPOSITS IN JAPAN - Amano K. (My University, 2006)
The Plio-Pleistocene Trophonopsis in northern Japan consists of seven species: T. kamchatkana (Dall), T. uyemurai (Yokoyama), T. sasae Sawada, T. vermeiji Amano, sp. nov., T. aff. densicostata Golikov in Golikov and Scarlato, T. aff. undocostata Golikov and Sirenko and T. sp.. Trophon toyamai Hatai and Nisiyama and T. kagaensis Hatai and Nisiyama are synonymous with Trophonopsis uyemurai. By the end of the early Pleistocene, T. uyemurai, T. sasae and T. vermeiji became extinct and T. aff. undocostata and T. sp. might have become extinct, owing to decrease of salinity in shallow water during the low stands of the glacial Pleistocene. © by the Palaeontological Society of Japan.
Keywords: JAPAN; MURICIDAE; PLEISTOCENE; PLIOCENE; TROPHONOPSIS; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен